The strategic capability of a shoe company from Brazil: the Olympikus case - Juliana Suzin; Claudio Reis Gonçalo; Yeda Swirski de Souza (Revista de Ciências da Administração : RCA, 2007)
The main objective in this article is to analyze how the opportunities and resources are identified and mobilized to assure conditions to a traditional industry to compete through innovation. In this study decisions and actions associated to enterprising and innovations are analyzed in the context of the traditional Brazilian Industry. In this context, the global production chains are evaluated, in particular, the behavior and performance of the Brazilian Shoe Industry. The study of one case of the shoe industry provides the empiric base to discuss the questions proposed. The analysis of one line from articles produced by Calçados Azaléia, one of the biggest shoe factories in Brazil, is made. The evidences are based on interviews proposed to the executives of the company in the years of 2005 and 2006 where secondary data helps to analyze the subject, shoe business sector and the company. The conclusion is that the case takes a ‘revolutionary’ perspective of competitiveness, through the launching of one product that allies technology, quality and design, assuming a new level on administrative innovation and a new strategic position at the dynamic value chain.